Relation between bioresorbable scaffold sizing using QCA-Dmax and clinical outcomes at 1 year in 1,232 patients from 3 study cohorts (ABSORB Cohort B, ABSORB EXTEND, and ABSORB II) - Yuki Ishibashi (2018)
© 2015 American College of Cardiology Foundation. Objectives This study sought to investigate the clinical outcomes based on the assessment of quantitative coronary angiography-maximal lumen diameter (Dmax). Background Assessment of pre-procedural Dmax of proximal and distal sites has been used for Absorb scaffold size selection in the ABSORB studies. Methods A total of 1,248 patients received Absorb scaffolds in the ABSORB Cohort B (ABSORB Clinical Investigation, Cohort B) study (N = 101), ABSORB EXTEND (ABSORB EXTEND Clinical Investigation) study (N = 812), and ABSORB II (ABSORB II Randomized Controlled Trial) trial (N = 335). The incidence of major adverse cardiac events (MACE) (a composite of cardiac death, any myocardial infarction [MI], and ischemia-driven target lesion revascularization) was analyzed according to the Dmax subclassification of scaffold oversize group versus scaffold nonoversize group. Results Of 1,248 patients, pre-procedural Dmax was assessed in 1,232 patients (98.7%). In 649 (52.7%) patients, both proximal and distal Dmax values were smaller than the nominal size of the implanted scaffold (scaffold oversize group), whereas in 583 (47.3%) of patients, the proximal and/or distal Dmax were larger than the implanted scaffold (scaffold nonoversize group). The rates of MACE and MI at 1 year were significantly higher in the scaffold oversize group than in the scaffold nonoversize group (MACE 6.6% vs. 3.3%; log-rank p < 0.01, all MI: 4.6% vs. 2.4%; log-rank p = 0.04), mainly driven by a higher MI rate within 1 month post-procedure (3.5% vs. 1.9%; p = 0.08). The independent MACE determinants were both Dmax smaller than the scaffold nominal size (odds ratio [OR]: 2.13, 95% confidence interval [CI]: 1.22 to 3.70; p < 0.01) and the implantation of overlapping scaffolds (OR: 2.10, 95% CI: 1.17 to 3.80; p = 0.01). Conclusions Implantation of an oversized Absorb scaffold in a relatively small vessel appears to be associated with a higher 1-year MACE rate driven by more frequent early MI. (ABSORB Clinical Investigation, Cohort B [ABSORB Cohort B], NCT00856856; ABSORB EXTEND Clinical Investigation [ABSORB EXTEND], NCT01023789; ABSORB II Randomized Controlled Trial [ABSORB II], NCT01425281)